Teaching the museum careers in museum education - Melber, Leah M. (The AAM Press, American Alliance of Museums Press, 2014)
"Education departments in museums of all kinds serve millions of students and adult learners every year, using the objects and other resources of the museum to teach and inspire. The rapidly growing field of museum education provides hands-on, experiential learning, with museum educators often working closely with local school boards to supplement and enhance public school curricula. In Teaching the Museum, twenty contributors from across the exciting field of museum education offer innovative insights, anecdotes, and advice for best practices on how to realize the museum's full potential as an educational institution. From the balance between education and entertainment; to meeting the needs of both one's audience and the collection; to understanding connections between how we learn and how exhibits and programming are designed; this book will appeal to museum educators, students, and teachers seeking to learn more about the field"--Provided by publisher.